The Effect of Retinoic Acid on Development of Chicken Embryos - Kawakeb Saad; Eman Asageer (AlQalam Journal of Medical and Applied Sciences, 2023)
Background and aims. Retinoic acid (RA) is important morphogen for promoting normal vertebrate development, its work in critical gradient in most organs and tissues. Exogenous of RA can cause malformation in these organs and tissues. The current study aimed to find out the effect of application of different concentrations 6 ,10mg/ ml of retinoic acid dissolved in dimethyl sulphoxide (DMSO) on chicken development at different embryonic stages. Methods. Fertile domestic Gallus gallus eggs sullied from local poultry farm, eggs were cleaned and sterilized, then divided into two groups of experiments, one group for each concentration. Each experiment contains three groups, 10 eggs for each. These groups repeated four time for four different stages HH8, HH10, HH15 and HH18. Eggs were incubated in the incubation for require stage, then removed from incubation and injected with RA or (DMSO) in air sac or kept without injection as untreated control, then eggs were incubated for another 24 h. Eggs were opened after 24 and 48 h of incubation, survive embryos were collected and evaluated morphologically and histologically. Results. The study showed that RA cause general growth retardation. In addition, it causes, microcephaly, cranial bifida, cardiomegaly, forelimb induction, straight trunk. The degree of malformation depended on the developing stage and RA concentration, were malformation increases with high concentration and early stages. Significant effects observed in embryos treated with 10mg/ml at early stage. Moreover, effects of RA in HH8 and HH10 was sharper than that observed at embryos injected at HH15 and HH18 in two concentrations. Conclusion. This study demonstrates that exogenous RA treatment at doses above those necessary to ensure normal embryonic development results in severe abnormalities. This suggests that the embryonic response to rheumatoid arthritis is extremely sensitive, particularly during fetal neurogenesis.